Awans zawodowy w opinii nauczycieli szkół bydgoskich – uwarunkowania pedeutologiczne - Ostrowski, Kazimierz (Wydawnictwo Naukowe UAM Poznań, 2008)
This article analyses introduced model of teachers’ development. The research was conducted in order to obtain the opinion about: the forms of constant education; the updating of teaching and educational knowledge; the way of perfoming the basic duties and the restrictions connected with it; the forms of work of examination boards in the objectivity of their actions; the usage of pedagogical theories in the process of professional development. The author points out that the professional development is a long-term process. The process that is designed to use pedagogical knowledge in order to improve the quality of teachers’ work and to excel pedagogical supervision. The carried out research shows us how important is the development of teachers’ competence. In the article the author also included, from the carried out research, the most important pedagogical directives.
The professional career in the opinion of Bydgoszcz school teachers – pedeutological factors